Positive Epstein-Barr virus polymerase chain reaction in a case of acute retinal necrosis - Hamam, Rola N. (2012)
Epstein-Barr virus (EBV) is a ubiquitous DNA virus of the Herpesvirus genus. Its role in the pathogenesis of ocular disease is still controversial. We report a case of biopsy-proven EBV acute retinal necrosis (ARN) not associated with systemic mononucleosis that was diagnosed in a patient on immune-modulatory therapy for presumed autoimmune inflammation. A 46-year-old male presented with chronic uveitis of 8 months' duration that was affecting the left eye. The inflammation was unresponsive to treatment with high-dose systemic corticosteroids, methotrexate, cyclosporine, and intravitreal corticosteroid injections. On presentation, visual acuity was 6/24 in the left eye with an intraocular pressure of 17 mm Hg, white conjunctiva, and fine keratic precipitates. He had panuveitis with significant vitreous haze and retinal necrosis nasally (Fig. 1). Diffuse retinal vasculitis and profuse leakage from the optic disc were detected by fluorescein angiography (Fig. 2). The venereal disease research laboratory (VDRL) test, the Treponema pallidum haemagglutination (TPHA) test, human immunodeficiency virus, and purified protein-derivative tests were negative. Serum IgG titers were positive for Toxoplasma, herpes simplex virus (HSV), and varicella zoster virus (VZV). The patient had traveled overseas, so an aqueous tap was done with polymerase chain reaction (PCR) negative for HSV and VZV in January 2010. The patient was started on 1 gram twice daily of valacyclovir hydrochloride and 800/160 mg trimethoprim/sulfamethoxazole twice daily. Two months after initiation of treatment he developed retinal detachment with hand-motion vision. He underwent phacoemulsification with intraocular lens implantation, scleral buckling, pars plana vitrectomy, endolaser, and silicone oil fill in March 2010. Nondiluted vitreous was analyzed by PCR using the LightCycler EBV Quant Kit (Roche Diagnostics, Indianapolis, IN) and was positive for EBV (5150 copies per mL) and negative for HSV, VZV, and cytomegalovirus. The assay quantitative range was 1.0 × 103 - 2.0 × 107 copies per mL using 200 μL of plasma with the lower limit of detection being 500 copies per mL. The test was performed at the American University of Beirut Molecular Diagnostic Lab and confirmed by Bioscientia Reference Laboratories (Ingelheim, Germany). The patient was maintained on 1 gram twice daily of valacyclovir hydrochloride for 6 months. The area of retinal necrosis scarred down without progression or inflammation. Final corrected visual acuity was 6/30 1 year after surgery.